A Brief Review on Electro-generated Hydroxyl Radical for Organic Wastewater Mineralization - Ervin Nurhayati (Jurnal Sains & Teknologi Lingkungan, 2012)
Hydroxyl radical is a highly reactive oxidizing agent that can be electrochemically generated on the surface of Boron doped diamond (BDD) anode. Once generated, this radical will non-selectively mineralize organic pollutants to carbon dioxide, water and organic anions as the oxidation products. Its application in Advanced Oxidation Process (AOP) to degrade nonbiodegradable even the recalcitrant pollutants in wastewater has been increasingly studied and even applied.